Ultra low noise, current to voltage converter with offset compensation independent of the source impedance - Ciofi, Carmine; Festa, G.; Giannetti, Romano; Neri, Bruno (Sin editorial (Saint Paul, Estados Unidos de América))
A new version of a low-noise, high gain transimpedance amplifier, operating in the frequency range from DC to KHz, is described. The new version of the instrument, thanks to a completely differential architecture, is capable to give the same stability without controlling the temperature of the input stage, as in the previous one. A more sophisticated circuitry for offset nulling allows to null contemporaneously both voltage and current input offset sources. A further improvement of the performance, as far as low frequency noise is concerned, has been obtained. In fact, for instance, the input equivalent current noise is 5.2 fA//spl radic/Hz between 10 mHz and 2 Hz.
Capítulos en libros
Keywords: Instituto de Investigación Tecnológica (IIT)